Academic mobility - Maadad, Nina.; Tight, Malcolm (Bingley, U.K. : Emerald, 2014)
This book offers a contemporary perspective on the mobility of academics across the globe. With contributions from authors based across 4 continents focusing on the experience of academic mobility in Africa, Australia, Europe, the Gulf and the United States, the volume is both comprehensive and relevant.
Editorial Introduction / Nina Maadad, Malcolm Tight -- Being an international academic : a phenomenological study of academic migrants adjusting to working and living in Scotland / Carolin Kreber, Jenny Hounsell -- Mobilised by mobility? Determinants of international mobility plans among doctoral candidates in Germany / Nicolai Netz, Steffen Jaksztat -- Beyond diaspora : the lived experiences of academic mobility for educational researchers in the European higher education area / Fiona Hallett, Mustafa Yunus Eryaman -- The impact of mobility on the lives and careers of female and male academics in higher education / Magdalena Suárez-Ortega, Angelica Risquez -- Patterns and persistence in academic migration : 40 Years of Australian academic migration / Anthony Potts -- Academic mobility and migration : reflections of international academics in Australia / Chinthaka Balasooriya ... [et al.] -- Global academics moving down under : living and learning a new academic culture / Nina Maadad -- English and the academy for African skilled migrants : the impact of English as an 'academic lingua franca' / Ellen Hurst -- Academic expatriation : experiences from within the United Arab Emirates / Kay Sanderson -- Insights into the successful integration of foreign-born faculty in Israeli academia : the empowering effect of in-group ethno-cultural similarity / Ya'arit Bokek-Cohen, Nitza Davidovitch -- "Sensitive fences" : the im/mobility of working-class academics / Signe M. Kastberg -- The protection of the right to academic mobility under International Human Rights Law / Klaus Beiter.
Includes index.
Print version record
Keywords: Education -- Higher; Education -- General; Higher & further education, tertiary education; Education; College teacher mobility